PROGRAM PENDIDIKAN KECAKAPAN LITERASI KOMPUTER MELALUI MAGANG TRADISIONAL MASA PENDEMI COVID-19 - Mustakim Mustakim; Hamim Farhan; Ode Mohamad Man Ladamay; Risky Mila Sary; Utami Nurlali (Comm-Edu (Community Education Journal), 2020)
Digital literacy in the face of a new normality for the people's choice menjali daily activities. Computer literacy skills education pandemic period covid-19 learners equality peket C is a new experience trainee (student). This study aims to describe the management of computer literacy skills education program and an overview of the traditional fingering patterns of computer literacy skills education pandemic period covid-19. The research method used is a qualitative method with an ethnographic approach. This research analyzes using the method of data collection, simplification of data, and presentation of data, as well as conclusions and verification. This study Response 20 apprentices equality Package C in SKB Cerme Gresik. The research result shows that as the use of digital technology, the mastery of computers and networks, as well as information. The results of this study illustrate that the management of future pandemic computer literacy program covid-19 in general by using an online home.